Female labor force participation and the big five - Laura Wichert; Winfried Pohlmeier (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
This paper investigates the relationship between personality traits and female labor force participation. While research on the role of cognitive skills for individual labor market success has a long tradition in economics, comparatively little is known about the channels through which non-cognitive skills affect individual labor market behavior. There is striking evidence that personality traits play a major role in explaining individual differences in school attendance and school performance. However, comparatively little is known about how and which personality traits effect labor supply decisions. In this paper, we relate personality traits to preference parameters using a conventional structural framework of labor force participation. This allows us to separate the direct effects of personality traits affecting the individual participation decision through different individual preferences from the indirect effects through wages. We can show that personality traits play an important role in the female labor force participation decision. The channels through which personality traits effect labor force participation are manifold and depend on the specific trait. Aggregation of traits to a single index is therefore a suboptimal strategy.
Keywords: C35; J22; J24; 330; personality traits; female labor supply; wages; Frauenerwerbstätigkeit; Arbeitsangebot; Persönlichkeitspsychologie; Schätzung; Deutschland